A kind of high-fidelity audio power cord and its preparation method
By covering the PVC insulating layer and protective shell on the audio power cord, combined with the use of flame retardant and thermal stabilizer, the problem of excessive power heating and thermal aging of the power cord is solved, and the thermal stability and flame retardancy of the power cord are improved, ensuring the normal use and safety of the audio.
Patent Information
- Application Number
- CN202410531892.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-29
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-04-29
AI Technical Summary
At this stage, the power cord is heated due to excessive power, and thermal aging affects the normal use of the audio, and may cause fires, reducing the safety of use.
A method of preparing a fidelity audio power cord is adopted. By covering the PVC insulating layer outside the metal copper wire core, and covering the protective shell outside the PVC insulating layer. The protective shell is composed of PVC masterbatch, flame retardant, heat stabilizer, antioxidant and plasticizer. The flame retardant is prepared through a specific chemical reaction, and the thermal stabilizer improves the stability of the PVC molecular chain by modifying the polyurea structure.
Effectively prevent the power cord from burning due to short circuit, improve the thermal stability and flame retardancy of the power cord, reduce the fire risk caused by heating, and ensure the normal use and safety of the audio.
Smart Images

Figure BDA0004818322500000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of power line preparation, and in particular to a high-fidelity audio power line and a preparation method thereof. Background Art
[0002] Audio refers to sounds other than human language and music, including sounds from the natural environment, sounds from animals, sounds from machines and tools, and various sounds from human movements. Audio probably includes power amplifiers and peripheral equipment, including compressors, effects, equalizers, VCDs and DVDs, etc. Speakers, sound boxes, speakers, mixers, microphones and display devices add up to a set. The power cord is an electric wire that transmits current. The structure of the power cord mainly includes an outer sheath, an inner sheath, and a conductor. Common transmission conductors include copper and aluminum metal wires. During use, high-power audio will cause the power cord temperature to rise due to its own power. Some power cords will experience thermal aging due to their poor thermal stability, which will affect the normal use of the audio. In severe cases, it may even cause a fire, greatly reducing the safety of use. Summary of the invention
[0003] The purpose of the present invention is to provide a high-fidelity audio power cord and a preparation method thereof, which solves the problem that the power cord at present is overheated due to excessive power and affects normal use, and cannot extinguish open flames.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a high-fidelity audio power cord comprises the following steps:
[0006] A PVC insulation layer is coated on the outside of a plurality of metal copper conductor cores, and a protective shell is coated on the outside of the PVC insulation layer;
[0007] The protective shell comprises the following raw materials in parts by weight: 100-120 parts of PVC masterbatch, 4-6 parts of flame retardant, 4-6 parts of heat stabilizer, 0.2-0.5 parts of antioxidant and 30-40 parts of plasticizer.
[0008] The PVC insulating layer has a molecular weight of 50000-60000, a polymerization degree of PVC masterbatch of 1800-2000, an antioxidant of one or more of antioxidant 1010, antioxidant 1035 and antioxidant 1076 mixed in any proportion, and a plasticizer of one or more of dioctyl adipate, dioctyl phthalate and epoxy soybean oil mixed in any proportion.
[0009] Further, the flame retardant is prepared by the following steps:
[0010] Step A1: 4-bromophenol, sodium hydroxide and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, hexachlorocyclotriphosphazene is added under the conditions of a rotation speed of 120-150 r / min and a temperature of 67-69° C., and the mixture is refluxed for reaction for 15-20 h to obtain intermediate 1, intermediate 1 is dissolved in tetrahydrofuran, n-butyl lithium is added under stirring at a rotation speed of 60-80 r / min and a temperature of minus 78° C., stirring is continued for 1-2 h, triisopropyl borate is added, reaction is carried out for 10-15 h, tetrahydrofuran is distilled off, the mixture is added to a hydrochloric acid aqueous solution, and stirring is carried out for 1-1.5 h to obtain intermediate 2;
[0011] Step A2: The intermediate 2, 3,4-dihydroxyphenylacetic acid, chloroform and 5A molecular sieve are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 150-200 r / min and a temperature of 62-65° C. for 10-15 hours, and then the filter residue is removed by filtration, 3-amino-1,2,4-triazole and DCC are added, and the reaction is continued for 6-8 hours to obtain the intermediate 3. The intermediate 3, cobalt chloride hexahydrate and DMF are mixed evenly, and the reaction is carried out at a temperature of 85-90° C. for 70-75 hours to obtain a flame retardant.
[0012] Furthermore, the molar ratio of 4-bromophenol, sodium hydroxide and hexachlorocyclotriphosphazene described in step A1 is 6.5:6.2:1, the molar ratio of intermediate 1, n-butyl lithium and triisopropyl borate is 1:6:7, and the mass fraction of the hydrochloric acid aqueous solution is 1-3%.
[0013] Furthermore, the usage ratio of the intermediate 2, 3,4-dihydroxyphenylacetic acid and 5A molecular sieve described in step A2 is 2.5mmol:15mmo l:2g, and the molar ratio of the intermediate 3 and cobalt chloride hexahydrate is 1:6.
[0014] Further, the thermal stabilizer is prepared by the following steps:
[0015] Step B1: Dimercaptopropanol, acrylic acid, benzophenone and DMF are mixed evenly, and reacted for 1-1.5 hours at a speed of 120-150 r / min, a temperature of 20-25° C. and irradiation with 365 nm ultraviolet light to obtain intermediate 4; intermediate 4, 3-amino-1,2,4-triazole, DCC and DMF are mixed evenly, and reacted for 3-5 hours at a speed of 150-200 r / min and a temperature of 30-40° C. to obtain intermediate 5;
[0016] Step B2: octamethylcyclotetrasiloxane, potassium hydroxide and dimethyl sulfoxide are mixed uniformly, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added under stirring at a speed of 120-150 r / min and a temperature of 90-95° C., and the temperature is raised to 110-115° C., and the reaction is carried out for 8-10 hours, and the pH is adjusted to neutral, and the temperature is lowered to 40-45° C., and the reaction is continued for 3-5 hours to obtain diamine polysiloxane;
[0017] Step B3: dissolve the diamine polysiloxane in toluene, stir and add dicyclohexylmethane diisocyanate at a speed of 60-80r / min and a temperature of 20-25°C, react for 20-30min, cool to 10-15°C, add intermediate 5, continue to react for 20-30min to obtain modified polyurea, dissolve the modified polyurea in dimethyl sulfoxide, add zinc acetate, react for 3-5h at a speed of 150-200r / min and a temperature of 60-65°C to obtain a thermal stabilizer.
[0018] Furthermore, the molar ratio of dimercaprol and acrylic acid in step B1 is 1:2, the amount of benzophenone is 0.2-0.5% of the mass of dimercaprol and acrylic acid, and the molar ratio of intermediate 4, 3-amino-1,2,4-triazole and DCC is 1:2:2.1.
[0019] Furthermore, the mass ratio of octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B2 is 20:3, and the amount of potassium hydroxide used is 2‰ of the mass of octamethylcyclotetrasiloxane.
[0020] Furthermore, the molar ratio of the diamine polysiloxane, dicyclohexylmethane diisocyanate and intermediate 5 described in step B3 is 1:2:2, and the molar ratio of the modified polyurea and zinc acetate is 1.5:1.
[0021] The beneficial effects of the present invention are as follows: a high-fidelity audio power cord prepared by the present invention has a plurality of metal copper wire cores coated with a PVC insulation layer, and a protective shell coated on the outside of the PVC insulation layer, wherein the protective shell comprises the following raw materials in parts by weight: a PVC masterbatch, a flame retardant, a heat stabilizer, an antioxidant and a plasticizer, wherein the flame retardant is reacted with 4-bromophenol and hexachlorocyclotriphosphate nitrile as raw materials, so that the phenolic hydroxyl group on the 4-bromophenol reacts with the chlorine atom site on the hexachlorocyclotriphosphate nitrile to obtain an intermediate 1, and the intermediate 1 is reacted with triisopropyl borate to obtain an intermediate 1. The bromine atom site of the intermediate is reacted with triisopropyl borate to obtain intermediate 2, and intermediate 2 is reacted with 3,4-dihydroxyphenylacetic acid to make the boric acid group on intermediate 2 react with catechol on 3,4-dihydroxyphenylacetic acid, and then reacted with 3-amino-1,2,4-triazole for dehydration, so that the carboxyl group reacts with the amino group on 3-amino-1,2,4-triazole to obtain intermediate 1, and intermediate 3 is coordinated with cobalt chloride hexahydrate to obtain a flame retardant. When the flame retardant is burned, phosphoric acid and polyphosphoric acid can be formed due to the organic phosphorus in the molecule. Salt and other substances accelerate the formation of the carbon layer by catalyzing the dehydration and decomposition of the polymer. The nitrogen and boron elements can increase the density of the carbon layer. The transition metal cobalt can reduce the emission of smoke and prevent the power line from burning due to short circuit. The heat stabilizer uses dimercaptopropanol and acrylic acid as raw materials. Under the condition of 365nm ultraviolet light, the thiol group on the dimercaptopropanol reacts with the double bond on the acrylic acid to obtain intermediate 4. The intermediate 4 is reacted with 3-amino-1,2,4-triazole to make the carboxyl group on the intermediate 4 react with 3-amino-1,2,4 -Triazole is subjected to dehydration reaction to obtain intermediate 5, octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane are subjected to ring-opening polymerization to obtain diamine polysiloxane, diamine polysiloxane is reacted with dicyclohexylmethane diisocyanate to form isocyanate phenol-terminated polyurea, intermediate 5 is added to terminate the reaction to obtain modified polyurea, and the modified polyurea is combined with zinc acetate to obtain a heat stabilizer, which contains a large amount of polyurea structure, and the nitrogen atoms on the polyurea structure can replace the unstable Cl atoms on PVC, thereby increasing the stability of the PVC molecular chain, and the metal organic framework of zinc can absorb the released HCl to terminate its autocatalytic effect, thereby preventing the power supply from being damaged by overheating due to excessive power, thereby affecting normal use. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Example 1
[0024] A method for preparing a high-fidelity audio power cord comprises the following steps:
[0025] A PVC insulation layer is coated on the outside of a plurality of metal copper conductor cores, and a protective shell is coated on the outside of the PVC insulation layer;
[0026] The protective shell comprises the following raw materials in parts by weight: 100 parts of PVC masterbatch, 4 parts of flame retardant, 4 parts of heat stabilizer, 0.2 parts of antioxidant and 30 parts of plasticizer.
[0027] The PVC insulating layer has a molecular weight of 50,000, a polymerization degree of PVC masterbatch of 1,800, an antioxidant of antioxidant 1010, and a plasticizer of dioctyl adipate.
[0028] The flame retardant is prepared by the following steps:
[0029] Step A1: 4-bromophenol, sodium hydroxide and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, hexachlorocyclotriphosphazene is added under the conditions of a rotation speed of 120 r / min and a temperature of 67°C, and the mixture is refluxed for reaction for 15 hours to obtain intermediate 1, intermediate 1 is dissolved in tetrahydrofuran, n-butyl lithium is added under stirring at a rotation speed of 60 r / min and a temperature of -78°C, stirring is continued for 1 hour, triisopropyl borate is added, reaction is carried out for 10 hours, tetrahydrofuran is distilled off, the mixture is added to a hydrochloric acid aqueous solution, and stirring is carried out for 1 hour to obtain intermediate 2;
[0030] Step A2: The intermediate 2, 3,4-dihydroxyphenylacetic acid, chloroform and 5A molecular sieve are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 150 r / min and a temperature of 62° C. for 10 hours. The filter residue is removed by filtration, 3-amino-1,2,4-triazole and DCC are added, and the reaction is continued for 6 hours to obtain the intermediate 3. The intermediate 3, cobalt chloride hexahydrate and DMF are mixed evenly, and the reaction is carried out at a temperature of 85° C. for 70 hours to obtain a flame retardant.
[0031] The molar ratio of 4-bromophenol, sodium hydroxide and hexachlorocyclotriphosphazene described in step A1 is 6.5:6.2:1, the molar ratio of intermediate 1, n-butyl lithium and triisopropyl borate is 1:6:7, and the mass fraction of the hydrochloric acid aqueous solution is 1-3%.
[0032] The usage ratio of the intermediate 2, 3,4-dihydroxyphenylacetic acid and 5A molecular sieve described in step A2 is 2.5 mmol:15 mmol:2 g, and the molar ratio of the intermediate 3 and cobalt chloride hexahydrate is 1:6.
[0033] The thermal stabilizer is prepared by the following steps:
[0034] Step B1: Dimercaptopropanol, acrylic acid, benzophenone and DMF were mixed evenly, and reacted for 1 hour at a speed of 120 r / min, a temperature of 20° C. and irradiation with 365 nm ultraviolet light to obtain intermediate 4; intermediate 4, 3-amino-1,2,4-triazole, DCC and DMF were mixed evenly, and reacted for 3 hours at a speed of 150 r / min and a temperature of 30-40° C. to obtain intermediate 5;
[0035] Step B2: octamethylcyclotetrasiloxane, potassium hydroxide and dimethyl sulfoxide are mixed uniformly, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added under stirring at a speed of 120 r / min and a temperature of 90° C., and the temperature is raised to 110° C., and the reaction is carried out for 8 hours, and then the pH is adjusted to neutral, and the temperature is lowered to 40° C. and the reaction is continued for 3 hours to obtain diamine polysiloxane;
[0036] Step B3: Dissolve the diamine polysiloxane in toluene, stir and add dicyclohexylmethane diisocyanate at a speed of 60 r / min and a temperature of 20°C, react for 20 minutes, cool to 10°C, add intermediate 5, and continue to react for 20 minutes to obtain modified polyurea. Dissolve the modified polyurea in dimethyl sulfoxide, add zinc acetate, and react for 3 hours at a speed of 150 r / min and a temperature of 60°C to obtain a thermal stabilizer.
[0037] The molar ratio of dimercaprol and acrylic acid in step B1 is 1:2, the amount of benzophenone is 0.2% of the mass of dimercaprol and acrylic acid, and the molar ratio of intermediate 4, 3-amino-1,2,4-triazole and DCC is 1:2:2.1.
[0038] The mass ratio of octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B2 is 20:3, and the amount of potassium hydroxide used is 2‰ of the mass of octamethylcyclotetrasiloxane.
[0039] The molar ratio of the diamine polysiloxane, dicyclohexylmethane diisocyanate and intermediate 5 in step B3 is 1:2:2, and the molar ratio of the modified polyurea and zinc acetate is 1.5:1.
[0040] Example 2
[0041] A method for preparing a high-fidelity audio power cord comprises the following steps:
[0042] A PVC insulation layer is coated on the outside of a plurality of metal copper conductor cores, and a protective shell is coated on the outside of the PVC insulation layer;
[0043] The protective shell comprises the following raw materials in parts by weight: 110 parts of PVC masterbatch, 5 parts of flame retardant, 5 parts of heat stabilizer, 0.3 parts of antioxidant and 35 parts of plasticizer.
[0044] The PVC insulating layer has a molecular weight of 50,000, a polymerization degree of PVC masterbatch of 2,000, an antioxidant of antioxidant 1035, and a plasticizer of dioctyl phthalate.
[0045] The flame retardant is prepared by the following steps:
[0046] Step A1: 4-bromophenol, sodium hydroxide and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, hexachlorocyclotriphosphazene is added under the conditions of a rotation speed of 120 r / min and a temperature of 69° C., and the mixture is refluxed for reaction for 15 h to obtain intermediate 1, intermediate 1 is dissolved in tetrahydrofuran, n-butyl lithium is added under stirring at a rotation speed of 80 r / min and a temperature of minus 78° C., stirring is continued for 2 h, triisopropyl borate is added, reaction is carried out for 13 h, tetrahydrofuran is distilled off, the mixture is added to a hydrochloric acid aqueous solution, and stirring is carried out for 1.5 h to obtain intermediate 2;
[0047] Step A2: The intermediate 2, 3,4-dihydroxyphenylacetic acid, chloroform and 5A molecular sieve are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 150 r / min and a temperature of 65° C. for 13 hours. The residue is filtered to remove the filter residue, 3-amino-1,2,4-triazole and DCC are added, and the reaction is continued for 7 hours to obtain the intermediate 3. The intermediate 3, cobalt chloride hexahydrate and DMF are mixed evenly, and the reaction is carried out at a temperature of 88° C. for 73 hours to obtain a flame retardant.
[0048] The molar ratio of 4-bromophenol, sodium hydroxide and hexachlorocyclotriphosphazene described in step A1 is 6.5:6.2:1, the molar ratio of intermediate 1, n-butyl lithium and triisopropyl borate is 1:6:7, and the mass fraction of the hydrochloric acid aqueous solution is 2%.
[0049] The usage ratio of the intermediate 2, 3,4-dihydroxyphenylacetic acid and 5A molecular sieve described in step A2 is 2.5 mmol:15 mmol:2 g, and the molar ratio of the intermediate 3 and cobalt chloride hexahydrate is 1:6.
[0050] The thermal stabilizer is prepared by the following steps:
[0051] Step B1: Dimercaptopropanol, acrylic acid, benzophenone and DMF were mixed evenly, and the mixture was reacted for 1.3 hours at a speed of 150 r / min, a temperature of 25° C. and irradiation with 365 nm ultraviolet light to obtain intermediate 4; intermediate 4, 3-amino-1,2,4-triazole, DCC and DMF were mixed evenly, and the mixture was reacted for 4 hours at a speed of 150 r / min and a temperature of 35° C. to obtain intermediate 5;
[0052] Step B2: octamethylcyclotetrasiloxane, potassium hydroxide and dimethyl sulfoxide are mixed uniformly, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added under stirring at a speed of 120 r / min and a temperature of 95° C., and the temperature is raised to 110° C., and the reaction is carried out for 9 hours, and then the pH is adjusted to neutral, and the temperature is lowered to 43° C., and the reaction is continued for 4 hours to obtain diamine polysiloxane;
[0053] Step B3: Dissolve the diamine polysiloxane in toluene, stir and add dicyclohexylmethane diisocyanate at a speed of 80 r / min and a temperature of 23°C, react for 25 minutes, cool to 13°C, add intermediate 5, and continue to react for 25 minutes to obtain modified polyurea. Dissolve the modified polyurea in dimethyl sulfoxide, add zinc acetate, and react for 4 hours at a speed of 200 r / min and a temperature of 63°C to obtain a thermal stabilizer.
[0054] The molar ratio of dimercaprol and acrylic acid in step B1 is 1:2, the amount of benzophenone is 0.3% of the mass of dimercaprol and acrylic acid, and the molar ratio of intermediate 4, 3-amino-1,2,4-triazole and DCC is 1:2:2.1.
[0055] The mass ratio of octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B2 is 20:3, and the amount of potassium hydroxide used is 2‰ of the mass of octamethylcyclotetrasiloxane.
[0056] The molar ratio of the diamine polysiloxane, dicyclohexylmethane diisocyanate and intermediate 5 in step B3 is 1:2:2, and the molar ratio of the modified polyurea and zinc acetate is 1.5:1.
[0057] Example 3
[0058] A method for preparing a high-fidelity audio power cord comprises the following steps:
[0059] A PVC insulation layer is coated on the outside of a plurality of metal copper conductor cores, and a protective shell is coated on the outside of the PVC insulation layer;
[0060] The protective shell comprises the following raw materials in parts by weight: 120 parts of PVC masterbatch, 6 parts of flame retardant, 6 parts of heat stabilizer, 0.5 parts of antioxidant and 40 parts of plasticizer.
[0061] The molecular weight of the PVC insulating layer is 60000, the polymerization degree of the PVC masterbatch is 2000, the antioxidant is antioxidant 1076, and the plasticizer is epoxy soybean oil.
[0062] The flame retardant is prepared by the following steps:
[0063] Step A1: 4-bromophenol, sodium hydroxide and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, hexachlorocyclotriphosphazene is added under the conditions of a rotation speed of 150 r / min and a temperature of 69° C., and the mixture is refluxed for reaction for 20 h to obtain intermediate 1, intermediate 1 is dissolved in tetrahydrofuran, n-butyl lithium is added under stirring at a rotation speed of 80 r / min and a temperature of minus 78° C., stirring is continued for 2 h, triisopropyl borate is added, reaction is carried out for 15 h, tetrahydrofuran is distilled off, the mixture is added to a hydrochloric acid aqueous solution, and stirring is carried out for 1.5 h to obtain intermediate 2;
[0064] Step A2: The intermediate 2, 3,4-dihydroxyphenylacetic acid, chloroform and 5A molecular sieve are mixed evenly, nitrogen is introduced for protection, and the reaction is carried out at a speed of 200 r / min and a temperature of 65° C. for 15 hours. The residue is filtered to remove the filter residue, 3-amino-1,2,4-triazole and DCC are added, and the reaction is continued for 8 hours to obtain the intermediate 3. The intermediate 3, cobalt chloride hexahydrate and DMF are mixed evenly, and the reaction is carried out at a temperature of 90° C. for 75 hours to obtain a flame retardant.
[0065] The molar ratio of 4-bromophenol, sodium hydroxide and hexachlorocyclotriphosphazene described in step A1 is 6.5:6.2:1, the molar ratio of intermediate 1, n-butyl lithium and triisopropyl borate is 1:6:7, and the mass fraction of the hydrochloric acid aqueous solution is 3%.
[0066] The usage ratio of the intermediate 2, 3,4-dihydroxyphenylacetic acid and 5A molecular sieve described in step A2 is 2.5 mmol:15 mmol:2 g, and the molar ratio of the intermediate 3 and cobalt chloride hexahydrate is 1:6.
[0067] The thermal stabilizer is prepared by the following steps:
[0068] Step B1: Dimercaptopropanol, acrylic acid, benzophenone and DMF were mixed evenly, and reacted for 1.5 hours at a speed of 150 r / min, a temperature of 25°C and irradiation with 365 nm ultraviolet light to obtain intermediate 4; intermediate 4, 3-amino-1,2,4-triazole, DCC and DMF were mixed evenly, and reacted for 5 hours at a speed of 200 r / min and a temperature of 40°C to obtain intermediate 5;
[0069] Step B2: octamethylcyclotetrasiloxane, potassium hydroxide and dimethyl sulfoxide are mixed uniformly, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added under stirring at a speed of 150 r / min and a temperature of 95° C., and the temperature is raised to 115° C., and the reaction is carried out for 10 hours, and then the pH is adjusted to neutral, and the temperature is lowered to 45° C., and the reaction is continued for 5 hours to obtain diamine polysiloxane;
[0070] Step B3: dissolve the diamine polysiloxane in toluene, stir and add dicyclohexylmethane diisocyanate at a speed of 80 r / min and a temperature of 25°C, react for 30 minutes, cool to 15°C, add intermediate 5, and continue to react for 30 minutes to obtain modified polyurea, dissolve the modified polyurea in dimethyl sulfoxide, add zinc acetate, and react for 5 hours at a speed of 200 r / min and a temperature of 65°C to obtain a thermal stabilizer.
[0071] The molar ratio of dimercaprol and acrylic acid in step B1 is 1:2, the amount of benzophenone is 0.5% of the mass of dimercaprol and acrylic acid, and the molar ratio of intermediate 4, 3-amino-1,2,4-triazole and DCC is 1:2:2.1.
[0072] The mass ratio of octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B2 is 20:3, and the amount of potassium hydroxide used is 2‰ of the mass of octamethylcyclotetrasiloxane.
[0073] The molar ratio of the diamine polysiloxane, dicyclohexylmethane diisocyanate and intermediate 5 described in step B3 is 1:2:2, and the molar ratio of the modified polyurea and zinc acetate is 1.5:1.
[0074] Comparative Example 1
[0075] Compared with Example 1, this comparative example uses intermediate 2 to replace the flame retardant, and the other steps are the same.
[0076] Comparative Example 2
[0077] Compared with Example 1, this comparative example uses intermediate 3 to replace the flame retardant, and the other steps are the same.
[0078] Comparative Example 3
[0079] Compared with Example 1, this comparative example uses modified polyurea instead of thermal stabilizer, and the remaining steps are the same.
[0080] The protective shells prepared in Examples 1-3 and Comparative Examples 1-3 were pressed into samples of 100 mm × 15 mm × 5 mm. The test conditions were a nitrogen atmosphere with a nitrogen flow rate of 20 mL / min, a heating rate of 20°C / min, a test temperature range of 40-600°C, and a weight loss of 5% as the starting decomposition temperature. The combustion grade was tested according to the standard of ASTM D3801, and the sample was 100 mm × 15 mm × 5 mm. The oxygen index was tested according to the standard of GB / T20461-2008, and the sample was 100 mm × 15 mm × 5 mm. The test results are shown in the following table.
[0081]
[0082] It can be seen from the above table that the present invention has good thermal stability and flame retardancy.
[0083] The above contents are merely examples and explanations of the concept of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing a high-fidelity audio power cord, characterized in that: The specific steps include: A PVC insulation layer is coated on the outside of a plurality of metal copper conductor cores, and a protective shell is coated on the outside of the PVC insulation layer; The protective shell comprises the following raw materials in parts by weight: 100-120 parts of PVC masterbatch, 4-6 parts of flame retardant, 4-6 parts of heat stabilizer, 0.2-0.5 parts of antioxidant and 30-40 parts of plasticizer; The flame retardant is prepared by the following steps: Step A1: 4-bromophenol, sodium hydroxide and tetrahydrofuran are mixed evenly, nitrogen is introduced for protection, refluxed and hexachlorocyclotriphosphazene is added, refluxed to react, and intermediate 1 is obtained. Intermediate 1 is dissolved in tetrahydrofuran, stirred and n-butyl lithium is added, stirring is continued, triisopropyl borate is added, reacted, tetrahydrofuran is distilled off, and added to a hydrochloric acid aqueous solution, stirred to obtain intermediate 2; Step A2: The intermediate 2, 3,4-dihydroxyphenylacetic acid, chloroform and 5A molecular sieve are uniformly mixed, nitrogen is introduced for protection, and after the reaction, the filter residue is removed by filtration, 3-amino-1,2,4-triazole and DCC are added, and the reaction is continued to obtain the intermediate 3, and the intermediate 3, cobalt chloride hexahydrate and DMF are mixed for reaction to obtain a flame retardant; The thermal stabilizer is prepared by the following steps: Step B1: dimercaptopropanol, acrylic acid, benzophenone and DMF are mixed to react to obtain intermediate 4, and intermediate 4, 3-amino-1,2,4-triazole, DCC and DMF are mixed to react to obtain intermediate 5; Step B2: octamethylcyclotetrasiloxane, potassium hydroxide and dimethyl sulfoxide are mixed and stirred, and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane is added, and after heating, the pH is adjusted to neutral, and the temperature is lowered to continue the reaction to obtain diamine polysiloxane; Step B3: dissolve the diamine polysiloxane in toluene, stir and add dicyclohexylmethane diisocyanate, react, cool and add intermediate 5, continue to react to obtain modified polyurea, dissolve the modified polyurea in dimethyl sulfoxide, add zinc acetate, react to obtain a thermal stabilizer.
2. The method for preparing a high-fidelity audio power cord according to claim 1, characterized in that: The molar ratio of 4-bromophenol, sodium hydroxide and hexachlorocyclotriphosphazene described in step A1 is 6.5:6.2:1, and the molar ratio of intermediate 1, n-butyl lithium and triisopropyl borate is 1:6:
7.
3. The method for preparing a high-fidelity audio power cord according to claim 1, characterized in that: The usage ratio of the intermediate 2, 3,4-dihydroxyphenylacetic acid and 5A molecular sieve described in step A2 is 2.5mmol:15mmol:2g, and the molar ratio of the intermediate 3 and cobalt chloride hexahydrate is 1:
6.
4. The method for preparing a high-fidelity audio power cord according to claim 1, characterized in that: The molar ratio of dimercaprol and acrylic acid in step B1 is 1:2, the amount of benzophenone is 0.2-0.5% of the mass of dimercaprol and acrylic acid, and the molar ratio of intermediate 4, 3-amino-1,2,4-triazole and DCC is 1:2:2.
1.
5. The method for preparing a high-fidelity audio power cord according to claim 1, characterized in that: The mass ratio of octamethylcyclotetrasiloxane and 1,3-bis(3-aminopropyl)-1,1,3,3-tetramethyldisiloxane described in step B2 is 20:3, and the amount of potassium hydroxide used is 2‰ of the mass of octamethylcyclotetrasiloxane.
6. The method for preparing a high-fidelity audio power cord according to claim 1, characterized in that: The molar ratio of the diamine polysiloxane, dicyclohexylmethane diisocyanate and intermediate 5 described in step B3 is 1:2:2, and the molar ratio of the modified polyurea and zinc acetate is 1.5:
1.
7. A high-fidelity audio power cord, characterized by: Prepared according to any one of the preparation methods described in claims 1-6.
Citation Information
Patent Citations
Flame-retardant data connecting line and preparation method thereof
CN111675873A
Mineral cable and preparation method thereof
CN117936177A